THE APPRECIATION OF THE STUDENTS LEVEL OF METHODOLOGY TRAINING IN THE BASIC COURSE AT THE SUBJECT "VOLLEYBALL" - Constantin Ciorbă; Virgil Larionescu Moroşan (Editura Univeristatii "Stefan cel Mare" din Suceava, 2019)
The methodological training of students represents an important component in the future professional-pedagogical formation due to the fact that it facilitates the understanding of the actuating load in the initiation - fixation-consolidation of the elements and technical processes specific to volleyball. The completion and the appropriation of this component can be achieved with the help of the auxiliary apparatus allowing realistic observations on the technical evolutions.